THE EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION AT CV. SIMBAT JAYA MEDAN CAR RENTAL SERVICES - Ilma Auliza; Teuku Fahmi; Asrindah Nst (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
This study is entitled The Effect of Service Quality on Customer Satisfaction at CV. Simbat Jaya Car Rental Services in Medan. This research is motivated by the importance of service quality in determining customer satisfaction in the service sector. Service quality plays a crucial role in shaping customer perceptions and experiences when using services. Therefore, this study aims to determine the effect of service quality on customer satisfaction. This study uses a quantitative method with an associative approach. Data were collected through questionnaires distributed to 75 respondents. The data analysis techniques include validity test, reliability test, classical assumption test, simple linear regression analysis, and hypothesis testing. Data processing was carried out using SPSS to obtain accurate and reliable results. The results showed that service quality has a positive and significant effect on customer satisfaction. This is indicated by a significance value of 0.000. These findings indicate that better service quality leads to higher customer satisfaction. Thus, service quality has an important role in increasing customer satisfaction in car rental services. Based on the results, it can be concluded that service quality is a key factor in creating customer satisfaction. Therefore, companies are expected to continuously improve their service quality in order to maintain and enhance customer satisfaction sustainably.